Rhetorical and Picture Styles in the Works of Five Children Poets and Their use as Literature Teaching Materials in SMP (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This study explores the rhetorical and pictorial styles in the works of five prominent children's poets and evaluates their effectiveness as teaching materials in Iraqi junior high schools (SMP). The poets selected for analysis include A.A. Milne, Shel Silverstein, Dr. Seuss, Roald Dahl, and Jack Prelutsky, whose works are renowned for their unique linguistic and visual styles. By examining their poetry, the study aims to uncover how these elements contribute to the overall impact and educational value of the texts.Rhetorical styles in children's poetry often encompass a range of linguistic devices such as rhyme, rhythm, alliteration, and metaphor, which are designed to engage young readers and enhance their understanding of language. These devices not only make the poems enjoyable but also facilitate the development of phonological awareness, vocabulary, and interpretive skills. The visual components, including illustrations and typographic choices, complement the text and enrich the reading experience, making abstract concepts more accessible to children.The research employs a qualitative methodology, analyzing a selection of poems from each author to identify common rhetorical techniques and visual styles. The findings indicate that the integration of these elements in poetry significantly aids in capturing the interest of students and promoting a deeper appreciation for literature. Moreover, the study suggests practical strategies for educators to incorporate these poems into their teaching practices, emphasizing interactive and creative activities that align with the national curriculum.The conclusion underscores the importance of selecting high-quality literary works for educational purposes and highlights the potential of children's poetry to foster a lifelong love of reading. The study advocates for a more prominent place for poetry in the literature curriculum, encouraging teachers to leverage the unique styles of these poets to enhance literary education.